Bishop Christophe Munzihirwa: A Mushi, Congolese, and Pastor (Hekima Review, 2022)
Since his assassination on 29 October 1996,2 people have written articles, books, and doctoral dissertations on the Christian and Spiritual life of Christophe Munzihirwa. I want to present here the cultural roots of the force of his character, convictions, engagement,and Christian life. Because he was assassinated by invading Rwandese forces and their Congolese allies, it is only wise to use someanecdotes found in his own culture when distinguishing Bashi from their Rwandese neighbours. “Bamanya omushi oku mwami ashiga, omunyarwanda oku kabira kage.” It can be translated as: “A mushi is identified by his citizenship, but a Rwandese is identified by his ethnicity/tribe.”